Annotating modernism : marginalia and pedagogy from Virginia Woolf to the confessional poets - Golden, Amanda, 1979- (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2020)
Making extensive use of archival materials by Sylvia Plath, John Berryman, and Anne Sexton, Amanda Golden reframes the relationship between modernism and midcentury poetry. While Golden situates her book among other materialist histories of modernism, she moves beyond the examination of published works to address poets' annotations in their personal copies of modernist texts. A consideration of the dynamics of literary influence, Annotating Modernism analyzes the teaching strategies of midcentury poets and the ways they read modernists like T. S. Eliot, James Joyce, Ezra Pound, Virginia Woolf, and W. B. Yeats. Situated within a larger rethinking of modernism, Golden's study illustrates the role of midcentury poets in shaping modernist discourse.
OCLC-licensed vendor bibliographic record.
Keywords: Modernism (Literature) -- History and criticism; Modernism (Literature) -- Influence; Poetry, Modern -- 20th century -- History and criticism; Literature, Modern -- 20th century -- History and criticism